Assessment of the Sheffield Support Snood, an innovative cervical orthosis designed for people affected by neck muscle weakness. (February 2016) - Pancani, Silvia; Rowson, Jennifer; Tindale, Wendy; Heron, Nicola; Langley, Joe; McCarthy, Avril D.; Quinn, Ann; Reed, Heath; Stanton, Andrew; Shaw, Pamela J.; McDermott, Christopher J.; Mazzà, Claudia
Abstract: Background: This study aimed at quantifying the biomechanical features of the Sheffield Support Snood, a cervical orthosis specifically designed for patients with neck muscle weakness. The orthosis is designed to be adaptable to a patient's level of functional limitation using adjustable removable supports, which contribute support and restrict movement only in desired anatomical planes. Methods: The snood was evaluated along with two commercially available orthoses, the Vista and Headmaster, in a series of flexion, extension, axial-rotation and lateral flexion movements. Characterization was performed with twelve healthy participants with and without the orthoses. Two inertial-magneto sensors, placed on the forehead and sternum, were used to quantify the neck's range of motion. Findings: In its less supportive configuration, the snood was effective in limiting movements to the desired planes, preserving free movement in other planes. The Headmaster was only effective in limiting flexion. The range of motion achieved with the snood in its rigid configuration was equivalent ( P > 0.05, effect size < 0.4) to that achieved with the Vista, both in trials performed reaching the maximum amplitude (range of motion reduction: 25%–34% vs 24%–47%) and at maximum speed (range of motion reduction: 24%–29% vs 25%–43%). Interpretation: The Sheffield Support Snood is effectively adaptable to different tasks and, in its most supportive configuration, offers a support comparable to the Vista, but providing a less bulky structure. The chosen method is suitable for the assessment of range of motions while wearing neck orthoses and is easily translatable in a clinical context. Highlights: A protocol to assess cervical orthoses using inertial magneto units is proposed. A customisable orthosis for progressive neck muscle weakness is presented. The new orthosis and two other orthoses were compared in healthy adults. The protocol allowed a quantification of the main differences between the orthoses. The new orthosis allows selective support of movements along the chosen directions.